Bibliometric Analysis of Work Life Balance on Employee Performance (Jurnal Multidisiplin West Science, 2025)
The purpose of this research is to learn more about matters related to an employee's work and personal life, including work-life balance, time balance, and satisfaction balance. For the literature analysis in this study, the Science Direct database was used to screen articles published from 2015-2025 through a bibliometric study. 412 articles were found according to the predefined criteria with keywords such as work-life balance and health. Data were analyzed using Vosviewer. The results explain how to analyze Co-authorship, Co-occurrence, and Citation. It is hoped that this research will be useful for further research on the issue of work-life balance (also known as work-life balance).
Keywords: Employee Performance; Work Life Balance; Employee Welfare; Personal Life; Bibliometrics